(untitled) (Historias, 2004)
This paper draws the attention to the significance of time in the curricula of the Real Seminario de Mineria. Time, captured through the representation of the school calendar, was the expression of every collective activity and established the sequence and rate in which school chores, ceremonies and festivities should be performed.